The Power of the Plan : Building a University in Historic Columbia, South Carolina - Galehouse, Richard F. (Book collections on Project MUSE., 2019)
"The contemporary American university is many things: a center of traditional undergraduate learning, a focus for scholarship and research, a source of state and local pride and prestige (often due to success on the athletic fields), and an important engine of economic development. The physical place where this all occurs, the campus, conjures familiar images of quadrangles, dorms, lecture halls and libraries, and yes, ivy-covered walls. The best campuses foster a strong sense of place, often through memorable public spaces and a few iconic buildings, and a cohesive and contextually sensitive use of materials. Yet today's campuses are increasingly complicated and intertwined with their surrounding communities, both physically and economically. The modern research university, particularly in its state-flagship form, is a small city in itself, one that must fit within a complementary, but distinct, social and economic milieu. From an urban-planning standpoint, this is a mighty challenge. Addressing the programmatic requirements of the institution itself is hard. Doing so in a way that not only mitigates the impact on the surrounding community, but advances opportunity and quality of life in the metropolitan area is sufficiently complex to have emerged as a distinctive specialty within the urban-planning field. This challenge has also expanded the role of university officials, who must not only raise the resources to help their institution adapt and change but must also develop new leadership skills and organizational capacities in real estate investment and development, planning and urban design, the management and programming of public spaces, and community relations"--